2021
DOI: 10.3389/fped.2021.659164
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Severe Pneumonia in Children in Alveolar Lavage Fluid Using a High-Throughput Gene Targeted Amplicon Sequencing Assay

Abstract: Objective: To evaluate the diagnostic value of a high-throughput gene targeted amplicon sequencing (TAS) assay for detecting pathogenic microorganisms in alveolar lavage fluid (ALF) from children with severe community-acquired pneumonia (SCAP).Methods: A retrospective study was performed on 48 frozen ALF samples from 47 severe pneumonia cases admitted to Children's Hospital of Fudan University from January 1, 2019, to March 31, 2019. All samples were tested by a multiplex PCR (Multi-PCR) assay and a TAS assay.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
2
9
1
Order By: Relevance
“…Meanwhile, the detection rates of MP, ADV, and FLUA by multi-PCR were as high as 96.7% (88/91), 79.1% (72/91), and 8.7% (8/91), respectively. Such high detection rates of MP and AVD from ALF samples has also been reported in previous studies based on next-generation high-throughput sequencing technologies ( 17 , 21 ). Hence, both the results of CT and multi-PCR had proved MP, ADV, and FLUA were the most common pathogens detected from the patients who received fiberscope intervention, consistent with previous findings ( 17 , 20 23 ).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Meanwhile, the detection rates of MP, ADV, and FLUA by multi-PCR were as high as 96.7% (88/91), 79.1% (72/91), and 8.7% (8/91), respectively. Such high detection rates of MP and AVD from ALF samples has also been reported in previous studies based on next-generation high-throughput sequencing technologies ( 17 , 21 ). Hence, both the results of CT and multi-PCR had proved MP, ADV, and FLUA were the most common pathogens detected from the patients who received fiberscope intervention, consistent with previous findings ( 17 , 20 23 ).…”
Section: Discussionsupporting
confidence: 85%
“…Such high detection rates of MP and AVD from ALF samples has also been reported in previous studies based on next-generation high-throughput sequencing technologies ( 17 , 21 ). Hence, both the results of CT and multi-PCR had proved MP, ADV, and FLUA were the most common pathogens detected from the patients who received fiberscope intervention, consistent with previous findings ( 17 , 20 23 ). Additionally, we found that the total positive rate of MP-IgM in these cases were 63.7% (51/80), and supported the PCR results to a certain extent (Data set S2).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In this retrospective study, the total detection rate of eight respiratory viruses by DFA was 20.3%, especially the detection rate of 17.9% in severe CAP cases, which was far lower than the results of our previous studies using molecular biological methods [ 13 15 ]. We believe this was related to the low sensitivity of DFA to nucleic acid detection methods.…”
Section: Discussioncontrasting
confidence: 77%